The evolution of the body responsible for preparing and monitoring the state budget and the budget system modernization project in Algeria - Sabeg, Nassima (International journal of economic perspectives, 2025)
This paper aims to shed light on the evolution of the institution responsible for preparing and monitoring the state budget in Algeria, while analyzing the budget system modernization project as part of the structural reforms in public finance. It explores the role of these updates from independence to the digital age in enhancing transparency and achieving financial efficiency. The study advocates for the continued reinforcement of governance principles and the establishment of a strong and sustainable national economy. The research adopts a historical-analytical approach to trace the development of budgetary bodies across various historical stages, with a focus on organizational and legislative transformations. It also employs a descriptive-analytical method to examine the reform and digitization of the budgetary system, through legal and technical analyses of relevant legislation and executive decrees, in addition to reviewing modern budgetary information systems. The findings reveal that Algeria's public finance modernization project is moving toward a more efficient and multi-year planning model, despite persistent challenges related to capacity building, information security, and systems integration.